Free choice of unfunded systems : a first assessment - Gabrielle Demange (Center for Economic Studies and ifo Institute (CESifo), 2005)
The first pillars of social security systems differ widely across European countries both in the contribution rate and intra-generational redistribution. What would the impact of these differences be if EU citizens had free access to all systems? This paper aims to highlight some basic features of this question in a very simple two-country model.
Keywords: H55; H87; 330; unfunded systems; intragenerational redistribution; free choice; Soziale Sicherung; Sozialversicherung; Umlageverfahren; Einkommensumverteilung; Sozialversicherungsbeitrag; Freizügigkeit; Abwanderung und Widerspruch; Zwei-Länder-Modell; Theorie